Preparation and characterization of PVDF-PVP-TiO2 composite hollow fiber membranes for oily wastewater treatment using submerged membrane system - Ong, Chi Siang (Taylor & Francis, 2015)
A series of polyvinylidene fluoride (PVDF) hollow fiber ultrafiltration membranes made of different titanium dioxide (TiO2) concentrations with the presence of polyvinylpyrrolidone as additive was prepared. The membrane performances were characterized in terms of pure water flux, permeate flux, and oil rejection, while the membrane morphologies were analyzed using scanning electron microscope and atomic force microscope. The experimental results showed that when 2 wt.% TiO2 was incorporated into PVDF membranes, optimized permeate flux and oil rejection of 70.48 L/m(2 )h (+/- 1.41) and 99.7% (+/- 0.3), respectively, could be obtained when tested using 250ppm synthesized oily solution under vacuum condition. Compared to the PVDF membrane without TiO2 addition, all the composite membranes showed relatively higher permeate flux and oil rejection. Based on the results obtained, it is reported that the composite PVDF membrane incorporated with 2 wt.% TiO2 exhibited the best separation performance in which complete removal of oil was able to achieve regardless of the feed oil concentration. However, decrease in permeate flux was observed when the feed oil concentration increased from 250 to 1,000ppm. The results concluded that the composite PVDF membrane showed better performance in treating oily solution compared to that of without TiO2.